(untitled) (Світ фінансів, 2019)
Довгань Ж. М. Підвищення ефективності діяльності банківських установ. Розглянуто теоретичні та практичні засади забезпечення ефективності банківської діяльності. Охарактеризовано основні тенденції прояву ризиків порушення ефективності банківської діяльності, тенденції ефективного розвитку та довгострокового зростання банківського сектору на сучасному етапі. Проаналізовано шляхи формування та впровадження інноваційних аспектів системи забезпечення ефективної роботи банків. Зроблено акцент на важливості співпраці банківських установ із фінтех-компаніями. Довгань Ж. Н. Повышение эффективности деятельности банковских учреждений. Рассмотрены теоретические и практические аспекты обеспечения эффективности банковской деятельности. Охарактеризованы основные тенденции проявления рисков нарушения эффективности банковской деятельности, тенденции эффективного развития и долгосрочного роста банковского сектора на современном этапе. Проанализированы пути формирования и внедрения инновационных аспектов системы обеспечения эффективной работы банков. Сделан акцент на важности сотрудничества банковских учреждений с финтех-компаниями. Dovhan Z. Increasing efficiency of the banking institutions activity. Introduction. The problems of banking efficiency improvement have become very important in the conditions of economic instability and the period of increasing competition in banking services market. It is being changed both the banking system structure, and the business processes which were formed in it. Such changes demand the new approaches to reserves searching and banking system optimization objects. The innovation in the banking sector, methods of innovative bank development are the main in modern conditions. The purposeof this article is to identify the need to develop and apply innovative approaches in banking institutions to ensure their effective operation. Results. The article deals with the theoretical and practical principles of ensuring the efficiency of banking activity. It is characterized the main tendencies of the risk manifestation violation of banking activity efficiency. The trends of an effective development and the long-term growth of banking sector nowadays are described. The ways of formation and implementation of the innovative aspects of bank effective work providing system are analyzed. Special attention is paid to the importance of the cooperation between banks and financial companies. Conclusions. The problems of the banking system providing efficiency can be addressed customer service innovative technologies and the new products and services implementation, such as: to use the advanced hardware and software, to increas efficiency of personalization and channel optimization, digital and biometric identification, to use the large data, intellectual property and expanded analytics, credit marketplays, and artificial intelligence, to improv integrated multi-channel delivery and new loyalty programs.